An Empirical Study of Pricing Strategies in an Online Market with High-Frequency Price Information - Sara Ellison; Christopher M. Snyder (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study competition among a score of firms participating in an online market for a commodity computer component. Firms were able to adjust prices continuously; prices determined how the firms were ranked and listed (lowest price listed first), with better ranks contributing to firms' sales. Using a year's worth of hourly data for individual firms, we estimate a model of price adjustment, characterizing the factors driving price changes and measuring how much these factors differ across firms (i.e., strategy heterogeneity). We find evidence of managerial inattention as a cause of the price inertia observed in the market. Using separate estimates of the pricing model for groups of related firms, we simulate counterfactuals involving different mixes of these groups.
Keywords: L11; C73; D21; L81; 330